Tanggapan siswa terhadap pemanasan yang dilakukan dengan modifikasi permainan tradisional - Astiati; Samodra, Tauvan Juni; Gustian, Uray (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
Warming up is always done by running or jogging around the field. Warming up like this is very monotonous to do, so it needs the creativity of Physical Education and Sports Health teachers in developing heating so that the heating indicator can be achieved and not monotonous. Warming up does not have to run around the field, warming up can be done by playing. The purpose of this study was to determine students' responses to the warm-up carried out by modifying traditional games. This research is a pre-experimental research using a one shot case study design. The research sample of students of SMP N 1 Selakau Timur and SMP N 03 Kubu amounted to 71 students. Data were collected in this study using a questionnaire containing seven questions. The questionnaire was filled out after warming up with six modifications to traditional games, namely, SOS level 1, SOS level 2, SOS level 3, Squirrel and Tree, Switching Star, and Catch So. The data obtained were analyzed using descriptive statistics. The results of the study show that 100% of this game is fun, 0% of this game is boring, 93% of this game is fun, 95.8% of this game is easy to understand, 97.2% of this game is easy to do, 98.6% of this game can improve enthusiasm to warm up, 91.5% warm-up with this game is more fun than jogging. It turns out that these six traditional game modifications can also increase the pulse rate to the training zone, with an average pulse rate of 67%.